2012
DOI: 10.1371/journal.pone.0050769
|View full text |Cite
|
Sign up to set email alerts
|

Using RosettaLigand for Small Molecule Docking into Comparative Models

Abstract: Computational small molecule docking into comparative models of proteins is widely used to query protein function and in the development of small molecule therapeutics. We benchmark RosettaLigand docking into comparative models for nine proteins built during CASP8 that contain ligands. We supplement the study with 21 additional protein/ligand complexes to cover a wider space of chemotypes. During a full docking run in 21 of the 30 cases, RosettaLigand successfully found a native-like binding mode among the top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 43 publications
0
49
0
Order By: Relevance
“…The atomic arrangements solved by direct methods present a unique opportunity for further improvement of our current estimates of electron scattering factors. Our atomic structures include hydrogen atoms, which play a central role in many biochemical processes; knowing their positions has provided important insights into catalytic mechanisms (33,34) and greatly aids rational drug design (35). Lastly, by using direct methods, MicroED can also provide ab initio solutions for smallmolecule organic compounds, such as rare pharmaceutical polymorphs (36) and designer peptoids (37) that challenge other means of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The atomic arrangements solved by direct methods present a unique opportunity for further improvement of our current estimates of electron scattering factors. Our atomic structures include hydrogen atoms, which play a central role in many biochemical processes; knowing their positions has provided important insights into catalytic mechanisms (33,34) and greatly aids rational drug design (35). Lastly, by using direct methods, MicroED can also provide ab initio solutions for smallmolecule organic compounds, such as rare pharmaceutical polymorphs (36) and designer peptoids (37) that challenge other means of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The study used crystallographic protein structures as inputs rather than comparative models. Kaufmann et al 42 demonstrated the predictive power of Rosetta ligand docking into Rosetta-built comparative models. In another study, RosettaLigand and AutoDock were used to dock 20 protein-ligand complexes 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the manuscript, we will refer to dedicated benchmark papers relevant to the individual steps to serve as references for expected Rosetta performance. In addition, Kaufmann and Meiler 42 recently performed a benchmark of ligand docking into comparative models with Rosetta, to which the reader is encouraged to refer for further information concerning RosettaLigand’s performance for ligand docking into comparative models.…”
Section: Introductionmentioning
confidence: 99%
“…The use of RosettaLigand [86,87] docking into homology models was benchmarked using nine protein-ligand complexes built during CASP8 [88], and other 21 additional complexes in order to expand the chemotype space. RosettaLigand found an acceptable native-like pose among the top ten scoring binding modes [89] in 21 out of 30 docking runs. It was also observed that docking performance depends more on template selection based on ligand occupancy than on target-template sequence identity.…”
Section: Retrospective and Prospective Docking Using Homology Modelsmentioning
confidence: 94%